ANALISIS ISI BUKU AJAR BAHASA INDONESIA BAGI PENUTUR ASING ‘BAHASAKU 1: AYO BICARA BAHASA INDONESIA’ - Julananda Putri Sahasti (MEDAN MAKNA: Jurnal Ilmu Kebahasaan dan Kesastraan, 2022)
Teaching material is crucial for any teaching and learning process, including the Indonesian Language for Foreign Speakers (BIPA). Thus, the textbook becomes the essential facilitator and acts as the deciding factor for the success of the BIPA program. This study aims to deeply explore the content of the textbook planned and designed by Alam Bahasa Indonesia. The findings of this study would contribute as a recommendation for other BIPA course institutions, tutors, and activists of BIPA in terms of the BIPA textbook. The research method applied was descriptive qualitative. Data gathering utilized comprehensive documentation of the textbook. The source textbook is BIPA ‘Bahasaku 1: Ayo Bicara Bahasa Indonesia’. The researcher became the critical instrument for data gathering and analysis. The results show that the textbook is printed in A4 size (21 x 29,7 cm) with a paper width of 80 gsm. The book consists of 10 units of lessons, and each has illustrated conversation, grammar focus in a text box, grammar exercises, cultural notes, and a vocabulary list. The materials included in every lesson unit are (1) target language grammatical structure; and  (2) materials in written text, topic, and exercises.